English: English - Banowati Azelia Putri Yuliawan; Bagja Waluya; Shandra Rama Panji Wulung (Centre For Tourism Planning and Development, 2023)
This study aims to determine the effect of environmental beliefs on the intention to visit ecological site through ecotourism attitude. The location of this research was conducted in Ciletuh-Palabuhanratu UGGp. In this study, the exogenous variable used were environmental beliefs with ecotourism attitude as the mediating variable and intention to visit ecotourism as the endogenous variable. The type of this research uses descriptive and verification with explanatory research methods. The sampling technique used was purposive sampling, amounting to 460 respondents. The data analysis technique in this study used Structural Equating Modeling (SEM). The results of this study indicate that the description of environmental belief, ecotourism attitude, and intention to visit ecotourism are in a fairly good category. The findings in this study suggest that environmental belief variables indirectly influence the intention to visit visit ecological through ecotourism attitude. The research recommend both of tourists and Ciletuh-Palabuhanratu UGGp to increase environmental belief and ecotourism attitudes in order to create positive tourist visiting intentions.